De novo Assembly and Characterization of the Fruit Transcriptome of Idesia polycarpa Reveals Candidate Genes for Lipid Biosynthesis - Li, Rong-Jun; Gao, Xiang; Li, Lin-Mao; Liu, Xiu-Lin; Wang, Zhou-Ya; Lü, Shi-you (Frontiers in Plant Science, 2016)
Idesia polycarpa, is a valuable oilseed-producing tree of the Flacourtiaceae family that has the potential to fulfill edible oil production and is also a possible biofuel feedstock. The fruit is unique in that it contains both saturated and unsaturated lipids present in pericarp and seed, respectively. However, the knowledge of triglyceride synthesis and storage in tissues outside of the seeds is poorly studied. To gain insight into the unique properties of Idesia polycarpa fruits lipid synthesis, biochemical and transcriptomic approaches were used to compare the lipid accumulation between pericarp and seed of the fruit. Lipid accumulation rates, final lipid content and composition were significantly different between two tissues. Furthermore, we described the annotated transcriptome assembly and differential gene expression analysis generated from the pericarp and seed tissues. The data allowed for the identification of distinct candidate genes and reconstruction of lipid pathways, which may explain the differences of oil synthesis between the two tissues. The results may aid for engineering alternative pathways for lipid production in non-seeds.